The Prognostic Value of some Epithelial-Mesenchymal Transition Markers and Metastasis-Related Markers in Human Transitional Cell Carcinoma of the Bladder (Baghdad Science Journal, 2018)
Recent reports provided evidence that epithelial to mesenchymal transition (EMT) and some matrix metalloproteinases (MMPs) contribute to the invasion and metastasis of cancer cells. This study investigated the expression pattern of some EMT markers (E-cadherin and Vimentin) and some MMPs (MMP-2 and MMP-9) in transitional cell carcinoma (TCC). Fifty five paraffin embedded biopsies were included in this study. Expression pattern of E-cadherin and Vimentin was evaluated by immunohistochemistry while cytoplasmic mRNA expression of both MMP-2 and MMP-9 were determined by in situ hybridization. The expression of all markers were significantly increased with the increase of patient's age (? 50 years), and furthermore an increase in men expression when compared to women. Interestingly, all healthy tissues showed positive E-cadherin expression while they did not show any expression of Vimentin, MMP-2 and MMP-9. E-cadherin expression decreased, whereas expression of Vimentin increased according to the grade and stage of the tumor. Similarly, both MMP-2 and MMP-9 expression were increased with the progression of TCC. The current study conclude that a decrease in E-cadherin together with increased Vimentin, MMP-2 and MMP-9 are significant markers that correlate with poor prognosis of TCC.